Physiotherapists' Attitudes and Perceptions of Multidisciplinary Team Approache in Musculoskeletal Rehabilitation in Saudi Arabia: A Cross-Sectional Study (International Journal of Physiotherapy, 2025)
Background: A Multidisciplinary health care team refers to a group of health professionals who collaborate for a particular patient population. However, there is little information on its implementation in Saudi Arabia. This study assessed physiotherapists' attitudes and perceptions of the multidisciplinary team (MDT) approach to musculoskeletal rehabilitation.Methods: A total of 374 physiotherapists who have at least one year of experience participated in this cross-sectional study. The Attitude Toward Health Care Team Scale, consisting of 14 items, was used to assess their attitudes toward MDT. The responses were scored on a five-point Likert scale ranging from one (strongly disagree) to five (strongly agree).Results: There was no significant association between attitude toward the MDT approach and gender, age, or years of clinical practice (p=0.124, 0.825, 0.734, respectively). There was a significant association between attitude toward the MDT and the highest level of physiotherapy degree (p= 0.002). There was no significant association between attitude toward MDT and the number of working days/week or the nature of cases handled/day (p=0.680, 0.580, respectively). There was a significant association between attitude toward the MDT and the workplace, region, number of working hours/day, and number of cases handled/day (p=0.000, 0.010, 0.000, 0.003, respectively).Conclusion: The Saudi physiotherapists had a positive attitude toward the MDT approach in musculoskeletal rehabilitation, especially the senior physiotherapists, who were more positive. Moreover, working 7-9 hours/day and handling only 4-6 cases/day, yet maintaining a positive attitude toward the MDT approach.